G-12=-7

Simple and best practice solution for G-12=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for G-12=-7 equation:


Simplifying
G + -12 = -7

Reorder the terms:
-12 + G = -7

Solving
-12 + G = -7

Solving for variable 'G'.

Move all terms containing G to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + G = -7 + 12

Combine like terms: -12 + 12 = 0
0 + G = -7 + 12
G = -7 + 12

Combine like terms: -7 + 12 = 5
G = 5

Simplifying
G = 5

See similar equations:

| 2x+5n=11 | | 10a-35=8a+1 | | 4(9r+8)=-17+3r | | -4-3(1-7f)=22 | | 14-6x+2(5x-7)-8x+13=7x-11 | | 7+3s=49 | | 40x-10=5+20x | | 4.8x-3.1=16 | | 6a+b+1=0 | | y=32x^2-16x-30 | | factory=32x^2-16x-30 | | 2(a-3)+3(a+5)=4(2a-1)-5 | | -5x-7x=32 | | 3y-9=-18+3 | | 2p/6+25=37 | | 3y-9=-12 | | 9x+8=9x+72 | | 14x+5=10x+7 | | -a-4=3a | | 21-7y=6(4y+3) | | 8-6d=12 | | 3y-9=-6+3 | | 7xn=3-5xn | | 8.4x+0.3(x-4)= | | 4.5(4*-12)=144 | | 3y-9=18+3 | | -35=-5+9(s+3) | | 6e+5(w-2)=23 | | 5w-3=-18 | | 3y-9=12+3 | | 2+3(x+1)=21 | | 18x+18=162 |

Equations solver categories